Interpretation of the issue of time and personality in Oydin Oydin Oydinyeva's lyrics - Asatjanova Iroda (Zien Journals, 2022)
This article will reveal the theme of the period and personality of the poet Oydin Oydin Oydinalieva. Poetic lyrics analyze the subject of war, poems depicting the tragedy of the last century in the 1970's and 1980's
Keywords: period; poetic image; lyrical hero; poetic expression